AIAA Scitech 2019 Forum 2019
DOI: 10.2514/6.2019-0300
|View full text |Cite
|
Sign up to set email alerts
|

Similitude between 3D cellular patterns in transonic buffet and subsonic stall

Abstract: This paper studies the similitude between the 3D cellular patterns which appears in the simulation of transonic buffet and subsonic stall phenomenon using RANS/URANS simulations. These wings are obtained from the extrusion of a 2D airfoil with an added sweep angle and periodic boundary conditions imposed at both ends. This numerical setup allows to study three-dimensional buffet on the simplest configuration possible. Numerical solutions exhibit three-dimensional flows in the form of buffet cells. The latter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
2
2
0
Order By: Relevance
“…Considering the whole buffet cycle in figure 12 we see the forward and backward movement of the separation location and the strict two-dimensionality of the shock-train patterns. The only indication of potentially larger-scale structures is the spanwise waviness of the transitional flow structures seen in figure 12(e), but these are a weak feature and are only present for a small part of the buffet cycle.Similar to the present study, no significant 3D structures were observed in experiments by[65] on a two-dimensional NASA CRM airfoil, however stall and buffet cells have been reported by[66,67] at spanwise whavelengths λ z > 1c for different airfoil geometries. One would have expected to see significant larger scale features already in the present wide-domain simulation in the case that stall/buffet-cell behaviour was relevant for this airfoil at this flow condition, although it is not possible to say for sure that they would not form in even wider computational domains.C.…”
supporting
confidence: 88%
“…Considering the whole buffet cycle in figure 12 we see the forward and backward movement of the separation location and the strict two-dimensionality of the shock-train patterns. The only indication of potentially larger-scale structures is the spanwise waviness of the transitional flow structures seen in figure 12(e), but these are a weak feature and are only present for a small part of the buffet cycle.Similar to the present study, no significant 3D structures were observed in experiments by[65] on a two-dimensional NASA CRM airfoil, however stall and buffet cells have been reported by[66,67] at spanwise whavelengths λ z > 1c for different airfoil geometries. One would have expected to see significant larger scale features already in the present wide-domain simulation in the case that stall/buffet-cell behaviour was relevant for this airfoil at this flow condition, although it is not possible to say for sure that they would not form in even wider computational domains.C.…”
supporting
confidence: 88%
“…In this case, although the overall lift coefficient is still increasing between these two incidences, a negative sectional lift-curve slope is expected at the outboard sections where the massive separation occurs. A link between buffet cells and stall cells has been reported by Plante, Dandois & Laurendeau (2019). In contrast at , separation can be observed over a wider spanwise area, with the S-shaped shock curvature occurring further inboard at around .…”
Section: Results and Analysissupporting
confidence: 53%
“…In the present calculation only about 8 periods were acquired due to the high CPU cost. The existence of buffet cells [46,32] [7] has been used. Indeed, this method is well adapted to study short data that are known to consist of sinusoids in white noise (e.g.…”
Section: Resultsmentioning
confidence: 99%